2020
DOI: 10.1111/jonm.13161
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of workplace incivility in nursing

Abstract: Aim This research aims to present a general summary of researches on workplace incivility in nursing using bibliometric indicators. Background Nurses regularly experience incivility from their working environment. However, evidence shows that it has significant potential for harmful consequences, both in terms of their health and in terms of productivity. Therefore, nursing and hospital managers have a crucial role in creation and maintenance of civil behaviour. Method(s) This research reports on a bibliometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…According to the framework of Andersson and Pearson (1999), our study revealed that this interpersonal process, which occurs day‐to‐day, not only impacts hospital nurses' wellbeing (i.e., increasing daily emotional exhaustion after work and reducing daily vitality and daily positive affect at bedtime) but also affects the culture of the unit, fostering a toxic dynamic of relationships within the workgroups. Considering the high prevalence of workplace incivility among nurses (Taşkaya & Aksoy, 2021), our results support previous evidence of similar diary studies and remark on the necessity to better acknowledge its theoretical interpersonal mechanisms in nursing (Blanco‐Donoso et al, 2019; Campana & Hammoud, 2015; Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the framework of Andersson and Pearson (1999), our study revealed that this interpersonal process, which occurs day‐to‐day, not only impacts hospital nurses' wellbeing (i.e., increasing daily emotional exhaustion after work and reducing daily vitality and daily positive affect at bedtime) but also affects the culture of the unit, fostering a toxic dynamic of relationships within the workgroups. Considering the high prevalence of workplace incivility among nurses (Taşkaya & Aksoy, 2021), our results support previous evidence of similar diary studies and remark on the necessity to better acknowledge its theoretical interpersonal mechanisms in nursing (Blanco‐Donoso et al, 2019; Campana & Hammoud, 2015; Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Another key theme is to better explore what nurse managers can do to deal with day‐to‐day incivility spirals within units (Taşkaya & Aksoy, 2021). Nurse managers can promote a healthy work environment to reduce nurse‐to‐nurse incivility from colleagues within units in hospitals by creating supportive practices of respect and appropriate behaviour, as opposed to incivility (Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, studies of original article type, letters to the editor, reviews, conference papers, case presentations, book chapters are followed [21]. Similar studies have been found in the literature [21][22][23].…”
Section: Discussionmentioning
confidence: 69%
“…It usually applies bibliometric tools (e.g., Bibliometrix R, Gephi, Pajek, CiteSpace, Leximancer, and VOSviewer) to analyze the publication trend, the top articles, primary contributors, and major theme and frontier topics in a given field ( 11 13 ). There are several existing bibliometric analysis about nursing topics ( 14 16 ). However, no study focused on bibliometric analysis to provide a state-of-the-art review for VS research in nursing field.…”
Section: Introductionmentioning
confidence: 99%